An empirical approach to evaluate creep responses in polymers and polymeric composites and determination of design stresses. (15th July 2016) - Song, Ruyue; Muliana, Anastasia H.; Palazotto, Anthony
Abstract: This study presents determination of design stresses for high temperature polymer PMR-15 and carbon fiber/PMR-15 composites. The main purpose is to support design of structural components made of polymeric composites for high temperature applications. At elevated temperatures, polymers and polymeric composites show significant creep responses. Depending on the loading conditions (stress and temperature levels) and duration of loading, both transient and steady state creep responses are observed. An empirical model that is typically used for describing transient and steady state creep behaviors for metals and alloys at elevated temperatures is adopted to model creep responses of PMR-15. The rationale behind choosing the model is that the macroscopic creep responses of PMR-15 at elevated temperature are similar to the ones of metals and alloys tested at high temperatures. This creep model has been successfully used to determine design stresses for various metals and alloys operating at elevated temperatures. In order to determine creep responses of carbon fiber/PMR-15 composites a rule of mixture approach is adopted. A design criterion, which is to limit the permanent deformation to 0.2%, is considered for both polymer and composites. The design stresses and design spaces that satisfy the above design criterion are constructed for PMR-15 polymer, unidirectional carbon/polyimide lamina and [0/90]S symmetric laminate. As expected the mechanical performance of PMR-15 can be improved by adding carbon fiber. The proposed design spaces are useful in determining the maximum capacity of the materials under various loading conditions and duration, taking into account creep behaviors in materials, during the component design process.